2004
DOI: 10.1523/jneurosci.2909-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Malfunction of Respiratory-Related Neuronal Activity in Na+, K+-ATPase α2 Subunit-Deficient Mice Is Attributable to Abnormal Cl-Homeostasis in Brainstem Neurons

Abstract: Naϩ , K ϩ -ATPase ␣2 subunit gene (Atp1a2) knock-out homozygous mice (Atp1a2 Ϫ/Ϫ ) died immediately after birth resulting from lack of breathing. The respiratory-related neuron activity in Atp1a2 Ϫ/Ϫ was investigated using a brainstem-spinal cord en bloc preparation. The respiratory motoneuron activity recorded from the fourth cervical ventral root (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 51 publications
7
98
2
4
Order By: Relevance
“…In view of the tight functional and structural coupling of KCC2 and the ␣2 subunit of the Na-K-ATPase (Ikeda et al, 2004), it is interesting that the upregulation of the membrane expression of KCC2 was paralleled by a quantitatively similar upregulation of the Na-K-ATPase which ultimately provides the energy for K-Cl cotransporters, including both KCC2a and KCC2b. The available data indicate that the latter isoform is required for the developmental E GABA shift, but little is known about the functional significance of KCC2a (Uvarov et al, 2007(Uvarov et al, , 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the tight functional and structural coupling of KCC2 and the ␣2 subunit of the Na-K-ATPase (Ikeda et al, 2004), it is interesting that the upregulation of the membrane expression of KCC2 was paralleled by a quantitatively similar upregulation of the Na-K-ATPase which ultimately provides the energy for K-Cl cotransporters, including both KCC2a and KCC2b. The available data indicate that the latter isoform is required for the developmental E GABA shift, but little is known about the functional significance of KCC2a (Uvarov et al, 2007(Uvarov et al, , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As a secondary-active transporter, KCC2 relies on the K ϩ gradient generated by the Na-K-ATPase, and it has been demonstrated that KCC2 interacts physically and functionally with the ␣2 subunit of the Na-K-ATPase (Ikeda et al, 2004). Notably, the surface expression of the ␣2 subunit in the CA1 was also increased after a neonatal seizure episode (1.89 Ϯ 0.18; n ϭ 8 samples from 7 pairs of saline-and kainate-injected animals; p ϭ 0.018) (Fig.…”
Section: B the Increase In The CLmentioning
confidence: 99%
“…79 These mice die at birth because of lack of spontaneous respiratory activity due to functional impairment of the brainstem respiratory neurons, probably as a result of elevated intracellular [Cl Ϫ ] that would switch the GABA response from hyperpolarization to depolarization; the data suggest a specific coupling between the ␣ 2 Na ϩ ,K ϩ -ATPase and the neuron-specific K ϩ -Cl Ϫ cotransporter, which excludes Cl Ϫ ions from the cytosol in respiratory center neurons. 80 A specific colocalization of the ␣ 2 isoform of the Na ϩ ,K ϩ pump with the Na ϩ /Ca 2ϩ exchanger in microdomains that overlie subplasmalemmal endoplasmic reticulum was demonstrated in cultured astrocytes, suggesting a specific functional role of this isoform also in the regulation of intracellular Ca 2ϩ , particularly in the endoplasmic reticulum. 81 Indeed, elevated levels of intracellular Ca 2ϩ ions as well as elevated stores of Ca 2ϩ in the endoplasmic reticulum were measured in cultured astrocytes from Atp1a2 Ϫ/Ϫ mice.…”
Section: Figmentioning
confidence: 93%
“…These databases contain experimentally observed phosphorylation sites identified largely by mass spectrometry-based proteomic studies (43,44 25 and Ser 26 showed the broadest occurrence with a presence in the most vertebrate KCC1, KCC2, and KCC4 family members (Fig. 1).…”
Section: Database Mining and Phylogenetic Pattern Of Kcc2mentioning
confidence: 99%
“…Expression Analyses of KCC2 Phospho-mutants-To study the role of the phosphorylated serines Ser 25 , Ser 26 , Ser 937 , Ser 1022 , Ser 1025 , and Ser 1026 , we generated two mutants of rat KCC2b for each phosphorylation site. This isoform was chosen because it is the major KCC2 protein in the mature brain (53).…”
Section: Database Mining and Phylogenetic Pattern Of Kcc2mentioning
confidence: 99%